2005
DOI: 10.1021/ja052842+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of 16 π Octaalkyltetraphenylporphyrins

Abstract: The oxidized octaethyltetraphenylporphyrin (1, OETPP) and the corresponding newly prepared octaisobutyltetraphenylporphyrin (3, OisoBuTPP) could be isolated from the reaction of OETPPLi2 (or OisoBuTPPLi2) with SOCl2. The X-ray analysis and the characteristic UV-vis spectra of 1 and 3 revealed that these are the first examples of 16 pi nonaromatic porphyrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 9 publications
2
85
0
2
Order By: Relevance
“…X-ray structural analysis revealed that this novel species is the most distorted known 16π porphyrin, in agreement with our working hypothesis. The reaction of 16π OiPTPP with LiBF 4 followed by Pd 2 (dba) 3 afforded the corresponding 18π OiPTPP palladium(II) complex. X-ray analysis revealed that this complex was highly distorted compared with its 18π OiBTPP palladium(II) complex counterpart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray structural analysis revealed that this novel species is the most distorted known 16π porphyrin, in agreement with our working hypothesis. The reaction of 16π OiPTPP with LiBF 4 followed by Pd 2 (dba) 3 afforded the corresponding 18π OiPTPP palladium(II) complex. X-ray analysis revealed that this complex was highly distorted compared with its 18π OiBTPP palladium(II) complex counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…While these types of porphyrinoids have been intensively studied, investigations on ordinary porphyrins with [4n]π core electrons are rare and the chemistry of this group of porphyrins is still in the stage of development due to their synthetic difficulty and unstable nature. Whereas several examples of the doubly reduced species (20 π-electron state) have been characterized [2], the doubly oxidized species (16 π-electron state) have been reported only recently, by us [3] and Vaid's group [4] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Other recent examples showing CH/π hydrogen bonds in clathrates are a CH 2 Cl 2 complex of a porphyrin derivative [104], a CH 3 CN complex of a metallomacrocyle [105], an ethyne complex of a benzoyltricamphor derivative [106], a dicyclopentadienylaluminum complex [107], tetraarylpyrenes [108], 3-amino-2-(4-dimethylaminophenyldiazenyl)-1-phenylbut-2-en-1-one [109], iron and nickel complexes of 4-p-tolyl-2,6-di(2-pyrazinyl)pyridine [110], [Cu 2 (4,4 -bpy) 5 [111], copper complexes with pyrazolylpyrimidines as ligands [112], and host-guest complexes of cucurbit [8]uril [113]. Toda wrote excellent reviews on this issue [114].…”
Section: Lattice Inclusion Type Clathratesmentioning
confidence: 99%
“…In recent years, the chemistry of isophlorins has been reactivated in light of its relevance to antiaromatic porphyrins. [12][13][14] Synthesis of pyrrole-bridged porphyrin rings 3 H-5 H is straightforward through Suzuki-Miyaura cross-coupling of 5,10-diaryl-15,20-dibromoporphyrin 1…”
Section: Jianxin Songmentioning
confidence: 99%